Impact From Mental Health Problem to Pregnant Woman: A Literatur Systematic Review - Natalia Pereira; Maria Cardoso dos Santos; Eugenia Carvalho de Araújo; Etelvina Jose Soares Tilman; Olandino Evaristo Obeno (Journal of International Multidisciplinary Research, 2024)
Teenage pregnancy is a complex global issue with a significant impact on maternal mental health. This study aims to conduct a Systematic Literature Review (SLR) analysis of the relationship between teenage pregnancy and maternal mental health, with a focus on the impact, influencing factors, and variations in findings based on geographic and cultural context. Literature searches were carried out through scientific databases such as PubMed, Google Scholar, and several international journals. Inclusion criteria included studies that addressed the impact of teenage pregnancy on maternal mental health, with analysis of factors influencing this relationship as well as variations in findings based on geographic and cultural context. This SLR analysis identified that teenage pregnancy consistently has a negative impact on maternal mental health, including increasing the risk of stress, anxiety and depression. Factors such as social support, social stigma, and economic conditions play an important role in influencing the mental health of teenage mothers. The variety of findings suggests that cultural norms, family structure, and global crises such as the COVID-19 pandemic may significantly influence the experience and impact of teen pregnancy. These findings highlight the need for a holistic approach in supporting the mental health of teenage mothers, including increasing access to affordable mental health services, strong social supports, and educational programs that strengthen community awareness. Evidence-based policy implications can help reduce the negative impact of teenage pregnancy on maternal mental health, by integrating cultural and contextual perspectives in interventions aimed at improving the well-being of teenage mothers worldwide.